Sharing stories: complex intervention for diabetes education in minority ethnic groups who do not speak English. Issue 7492 (17th March 2005) - Greenhalgh, Trisha; Collard, Anna; Begum, Noorjahan
Abstract: Objective To develop and refine a complex intervention for diabetes support and education in minority ethnic groups, delivered through bilingual health advocates. Design Action research framework—a variety of methods used in an emergent and developmental manner, in partnership with clinicians, managers, and service users, drawing especially but not exclusively on narrative methods. Setting Deprived inner London district. Interventions Development and evaluation of three components of the complex intervention: a group based learning set for bilingual health advocates, in which stories about clients with diabetes formed the basis for action learning; advocate led support and education groups for people with diabetes, which used personal stories as the raw material for learning and action; organisational support to help to develop these new models and embed them within existing services. Results Both advocate groups and user groups were popular and well evaluated. Through storytelling, advocates identified and met their own educational needs in relation to diabetes and the unmet needs of service users. In the advocate led user groups, story fragments were exchanged in a seemingly chaotic way that the research team initially found difficult to facilitate or follow. Stories were not so much told as enacted and were often centred on discussion of "what to do." Whereas some organisations welcomed, successfully implemented, and sustained the advocate led groups, others failed to do so. A key component of the complex intervention was organisational support. Conclusions An action research approach allowed engagement with an underserved group of health service staff and with hard to reach service users. The study produced subjective benefits to these groups locally as well as a worked-up complex intervention that will now be formally tested in a randomised controlled trial.